2016
DOI: 10.1093/cercor/bhw130
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Dendritic Spines in the Avian Vocal Motor Cortex Following Deafening Depends on the Basal Ganglia Circuit

Abstract: Deafening elicits a deterioration of learned vocalization, in both humans and songbirds. In songbirds, learned vocal plasticity has been shown to depend on the basal ganglia-cortical circuit, but the underlying cellular basis remains to be clarified. Using confocal imaging and electron microscopy, we examined the effect of deafening on dendritic spines in avian vocal motor cortex, the robust nucleus of the arcopallium (RA), and investigated the role of the basal ganglia circuit in motor cortex plasticity. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 76 publications
4
17
0
Order By: Relevance
“…Using confocal microscopy and 3D electron microscopy, we demonstrated the sensitivity of dendritic spine length and spine synapse number to auditory deprivation. Together with previous data on the effect of Area X lesions on deafening-induced vocal changes (Kojima et al 2013;Zhou et al 2017), we suggest that these striatal changes might contribute to adult vocal plasticity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Using confocal microscopy and 3D electron microscopy, we demonstrated the sensitivity of dendritic spine length and spine synapse number to auditory deprivation. Together with previous data on the effect of Area X lesions on deafening-induced vocal changes (Kojima et al 2013;Zhou et al 2017), we suggest that these striatal changes might contribute to adult vocal plasticity.…”
Section: Discussionsupporting
confidence: 85%
“…Dendritic spines were analyzed blindly as described by Zhou et al . (2017), using NeuronStudio software (Rodriguez et al . 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Genes related to synaptic transmission were differentially expressed across multiple pallial regions, including song regions RA, HVC, and LMAN as well as the non-song region NCL. Neuron spine-associated genes were upregulated across RA, Arco., and HVC, consistent with previous reports of altered spine dynamics in the song motor pathway following deafening (Peng et al, 2013(Peng et al, , 2012aTschida and Mooney, 2012;Zhou et al, 2017).…”
Section: Song System-wide Transcriptional Signatures Of Song Destabil...supporting
confidence: 92%
“…For the songbird, prior studies have identified a variety of circuit, cellular, and molecular mechanisms that may contribute to deafening-induced song-destabilization (Brainard and Doupe, 2000;Kojima et al, 2013;Mandelblat-Cerf et al, 2014;Peng et al, 2013Peng et al, , 2012aPeng et al, , 2012bScott et al, 2000;Tschida and Mooney, 2012;Wang et al, 1999;Watanabe et al, 2002;Zhou et al, 2017). These prior demonstrations, which have focused on a disparate set of song control structures and specific candidate mechanisms, motivated our interest in applying a circuit-wide and unbiased approach in this system to identify molecular responses to auditory deprivationinduced motor destabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation